Diagnostic assessment, therapeutic care and education pathways in persons with autism spectrum disorder in transition from childhood to adulthood: the Italian National Ev.A Longitudinal Project - Marco Valenti; Monica Mazza; Giuseppe Maurizio Arduino; Roberto Keller; Ilenia Le Donne; Francesco Masedu; Giovanna Romano; Maria Luisa Scattoni (Istituto Superiore di Sanità, 2023)
Introduction. The transition from childhood to adulthood is one of the main critical points in the network of services for taking care of people with autism spectrum disorder (ASD). Within the framework of the national research programs on autism, an exploratory longitudinal multicentre study was conducted. This research program, called "Ev.A Project (Developmental and Adult Age)", was proposed by the Italian National Institute of Health (Istituto Superiore di Sanità, ISS) and the aim was the development and testing of a diagnostic, therapeutic, assistance and educational pathway (PDTAE) for autism. Aim. The present study aimed to evaluate two impact outcomes of the care protocol: the response obtained by the ASD person, and the perception of the change in the family context. Methods. Participants underwent an initial clinical evaluation and then after one year. Over the course of the year, participants undertook a program of intervention. The measures of adaptive functioning, need for support, psychiatric symptomatology and family quality of life were used for the outcome assessment. Linear mixed models were constructed for each measure to estimate the explanatory/predictive behavior of the intensity of the interventions, adjusted for the participant's level of symptom severity. Results. The results estimate a main effect of Intervention Group (b=-27.22, p<0.001) and severity level (b=-41.87, p<0.001) on the adaptive functioning of the ASD person, but no effect on performance on the dimension of Family Quality of Life (b=0.523, p=0.455). Conclusions. The most significant predictor of the impact on the ASD person is the activation of the service network, which must take into account the level of severity of the presented symptoms.